The Trend of Online Shopping in 21st Century: Impact of Enjoyment in Tam Model - Cheema, Umair; Rizwan, Muhammad; Jalal, Rizwan; Durrani, Faiza; Sohail, Nawal (Asian Journal of Empirical Research, 2013)
Although the technology evolve over the years however people takes more time to accept it and adopt in their daily life. Lack of customer acceptance towards new technology remains a big challenge for the marketers. The internet users in Pakistan increase at a phenomenal rate during the last five years but the adoption of online shopping is still slow. The purpose of this research paper is to create a model on the based on technology acceptance model in order to find the other factors that influence online shopping intentions. A survey of 150 respondents that includes professionals from various fields and university students was conducted. With the help of regression analysis, the proposed model was assessed. The findings reveal that perceived ease of use and perceived enjoyment are the factors that affect online shopping intention. Surprisingly, the effect of perceived usefulness was not significant on online shopping intentions. This particular results demand to create awareness in the population regarding the benefits of online shopping. This paper also found that perceived ease of use has a significant positive effect on perceived usefulness.